Handbook of Plant Biotechnology 2004
DOI: 10.1002/0470869143.kc021
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Resistance to Herbicides

Abstract: Crop resistance can be generated through a selection process or the introduction of a gene via transformation. We will refer to the latter as engineered herbicide resistance. The literature contains numerous studies on engineered plant resistance to various herbicide classes. There is a large distinction between demonstrating a resistance phenotype in plants versus developing a commercial resistant crop that requires consistent performance under varying environmental conditions. Creating an herbicide resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 73 publications
0
42
0
1
Order By: Relevance
“…We have fitness studies underway with the wild-type, P106S (rr), and TIPS (RR, Rr) EPSPS mutants. However, if this fitness cost from decreased catalytic efficiency is offset, for instance, by gene duplication of the TIPS gene as required for commercial crops (CaJacob et al, 2004), then evolution of Roundup Ready-like E. indica may be expected in nature, especially in species exhibiting EPSPS gene amplification (for review, see Sammons and Gaines, 2014), where the tandem repeat nature of the duplication (Jugulam et al, 2014) may facilitate incorporation of the necessary point mutations, and gene duplication is free of fitness cost (Vila-Aiub et al, 2014). Therefore, the evolutionary recipe to high-level glyphosate resistance in weedy plant species under glyphosate selection may have these primary components:…”
Section: Will There Be Other Epsps Double Mutations In Nature?mentioning
confidence: 99%
“…We have fitness studies underway with the wild-type, P106S (rr), and TIPS (RR, Rr) EPSPS mutants. However, if this fitness cost from decreased catalytic efficiency is offset, for instance, by gene duplication of the TIPS gene as required for commercial crops (CaJacob et al, 2004), then evolution of Roundup Ready-like E. indica may be expected in nature, especially in species exhibiting EPSPS gene amplification (for review, see Sammons and Gaines, 2014), where the tandem repeat nature of the duplication (Jugulam et al, 2014) may facilitate incorporation of the necessary point mutations, and gene duplication is free of fitness cost (Vila-Aiub et al, 2014). Therefore, the evolutionary recipe to high-level glyphosate resistance in weedy plant species under glyphosate selection may have these primary components:…”
Section: Will There Be Other Epsps Double Mutations In Nature?mentioning
confidence: 99%
“…Glyphosate is absorbed readily through plant surfaces (Kirkwood et al 2000). Once taken up by plant leaves, the unique physicochemical properties of glyphosate allow its systemic translocation via the phloem, in a manner similar to that of the photoassimilate sucrose, to rapidly growing and stronger metabolic sink tissue (CaJacob et al 2004). Some early work indicated that most crops and weed species lack endogenous mechanisms for catabolism or detoxification of glyphosate, although a number of plant and weed species, mostly legume, are known to have biochemical activities that could convert glyphosate into less toxic compounds such as aminomethylphosphonic acid (AMPA; Reddy et al 2004Reddy et al , 2008.…”
Section: Glyphosate: a Potent Nonselective Herbicidementioning
confidence: 99%
“…Two basic strategies have been used to engineer GT crops, (a) expression of a transgene encoding a glyphosate-insensitive target enzyme, and (b) expression of transgene-encoding enzymes for glyphosate deactivation or detoxification (CaJacob et al 2004;Feng et al 2010a;Pollegioni et al 2011). The discovery of the chloroplast-localized enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EP-SPS) as the sole target of glyphosate (Steinrücken and Amrhein 1980) offered an opportunity for engineering GT crops through glyphosate-insensitive EPSPSs.…”
Section: Strategies For Engineering Glyphosate Tolerance In Cropsmentioning
confidence: 99%
See 2 more Smart Citations